Levosimendan’s Effects on Length-Dependent Activation in Murine Fast-Twitch Skeletal Muscle - Haug, Michael; Michael, Mena; Ritter, Paul; Kovbasyuk, Larisa; Vazakidou, Maria Eleni; Friedrich, Oliver (International Journal of Molecular Sciences, 2024)
Levosimendan’s calcium sensitizing effects in heart muscle cells are well established; yet, its potential impact on skeletal muscle cells has not been evidently determined. Despite controversial results, levosimendan is still expected to interact with skeletal muscle through off-target sites (further than troponin C). Adding to this debate, we investigated levosimendan’s acute impact on fast-twitch skeletal muscle biomechanics in a length-dependent activation study by submersing single muscle fibres in a levosimendan-supplemented solution. We employed our MyoRobot technology to investigate the calcium sensitivity of skinned single muscle fibres alongside their stress–strain response in the presence or absence of levosimendan (100 µM). While control data are in agreement with the theory of length-dependent activation, levosimendan appears to shift the onset of the ‘descending limb’ of active force generation to longer sarcomere lengths without notably improving myofibrillar calcium sensitivity. Passive stretches in the presence of levosimendan yielded over twice the amount of enlarged restoration stress and Young’s modulus in comparison to control single fibres. Both effects have not been described before and may point towards potential off-target sites of levosimendan.
CRIS-Team Scopus Importer:2024-06-21
Keywords: calcium sensitivity; levosimendan; MyoRobot; single muscle fibre; stress–strain